PENGEMBANGAN MEDIA VIDEO INTERAKTIF PENDEKATAN PEMBELAJARAN VAN HIELE PADA MATERI BANGUN RUANG SISI DATAR - Fatimah Azzahro; Mawarsari, Venissa Dian; Aziz, Abdul (Universitas Cokroaminoto Palopo, 2025)
The topic of mathematical geometry, which explores shapes such as cubes, rectangular prisms, prisms, and pyramids, often presents challenges for students, particularly in visualizing these shapes and relating them to real-life situations. These difficulties require a solution in the form of technology-based learning media capable of presenting material progressively and engagingly. The Van Hiele learning approach was selected as it offers a systematic framework for understanding geometric concepts, ranging from visualization to abstract comprehension. This study aims to develop interactive video media based on the Van Hiele approach for teaching three-dimensional geometric shapes to eighth-grade students. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of analysis, design, and development. Data analysis was conducted through needs assessments and validation by subject matter experts and media experts. The validation results show that the developed interactive video media received an average score of 86.80% from subject matter experts and 87.68% from media experts, with an overall average score of 87.24%. These findings indicate that the developed interactive video media is highly valid and ready to be used as an effective and enjoyable learning tool to enhance students' understanding of three-dimensional geometric shapes.